Estimates of some approximating characteristics of the classes of periodic functions of one and many variables - Romanyuk, A. S.; Romanyuk, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 517.5 We obtain the exact-order estimates for some approximating characteristics of the classes $\mathbb{W}^{\boldsymbol{r}}_{p,\boldsymbol{α}}$ and $\mathbb{B}^{\boldsymbol{r}}_{p,θ}$ of periodic functions of one and many variables in the norm of the space $B_{∞, 1}.$